Uptake of modern family planning methods among women receiving spontaneous post abortion care at Kuajok hospital, South Sudan: a cross-sectional study - Majok, Samuel Ajiek; Makunyi, Eliphas Gitonga; Onsongo, Lister (International Journal Of Community Medicine And Public Health, 2022)
Background: Improving women’s health through modern family planning to spontaneous post abortion care is a key to prevent unwanted pregnancy immediately after miscarriage, world health Organization indicates that spacing for six months period following miscarriage prevent earlier pregnancy. South Sudan ranks the lowest country with the prevalence rate of 5.5% nationwide. This study helped to uncover the factors contribute to the low uptake of modern family planning options among spontaneous post abortion patients in Kuajok hospital, provide evidence to ministry of health, policy makers and health care providers to improve modern family planning services. Methods: Study adopted a descriptive cross-sectional designed and data was collected from spontaneous post abortion patients to determine the prevalence of spontaneous post abortion in the study area. Results: Urban and rural have difference choice of modern family planning a total of 38.4% (481) of post abortion women had sort care at the hospital in the past one year revealed that they preferred modern family planning over the other methods. With a total of 17.9% (224) women utilized pills to manage their family sizes, while injectable accounted for 8.6% (108) used of modern family planning among spontaneous post abortion women in that year. The study also noted that male condom was equally popular as a preferred among population at 11.9% (149). Female condoms and cervical diaphragm were unpopular and none patients used them. Conclusions: Ministry of health, policy makers to increase awareness on modern family planning to spontaneous post abortions patients.